Impact of helminth co-infection and treatment on mycobacterial growth inhibition in UK migrants with TB infection - S. Anwar; C.F. Turienzo; L. Tsang; S.G. Smith; H. Fletcher; F. Toulza; J.M. Cliff; M. Brown; H.M. Dockrell (IJTLD Open)
BACKGROUND: TB and helminth infections are co-endemic in many parts of the world. This has led to the hypothesis that immunomodulation due to helminth infections could adversely affect the ability to control Mycobacterium tuberculosis infection. Anti-helminthic treatment has been associated with improved anti-mycobacterial cellular responses and decreases in the frequency of regulatory T-cells. We therefore investigated how control of mycobacterial growth and anti-mycobacterial immune responses are modulated in helminth and TB co-infected individuals using a mycobacterial growth inhibition assay (MGIA). METHODS: Migrants with eosinophilia or suspected/diagnosed helminth infection and/or TB infection (TBI) were recruited when attending University College London Hospitals (London, UK) and followed up after completing anti-helminthic treatment. Mycobacterial growth inhibition was assessed using the BACTEC™ MGIT™ system after 72 hours of co-culture of peripheral blood mononuclear cells (PBMC) with M. bovis bacille Calmette-Guérin (BCG) or M. tuberculosis Erdman. RESULTS: Anti-helminthic treatment reduced total and helminth-specific antibodies in helminth-infected and TBI–helminth co-infected individuals. Helminth-infected individuals displayed lower growth inhibition in the MGIA than those without helminth infections, and mycobacterial growth inhibition improved after anti-helminthic treatment. Blocking interleukin-10 (IL-10) and transforming growth factor-beta (TGF-β) improved mycobacterial growth inhibition, while blocking interferon-gamma (IFN-γ) did not alter growth inhibition. CONCLUSION: Infection with helminths such as Schistosoma mansoni and Strongyloides spp. may reduce the ability to control mycobacterial growth.